Donor Complications Following Laparoscopic Compared to Hand-Assisted Living Donor Nephrectomy: An Analysis of the Literature - Whitney R. Halgrimson; Jeffrey Campsen; M. Susan Mandell; Mara A. Kelly; Igal Kam; Michael A. Zimmerman (Journal of Transplantation)
There are two approaches to laparoscopic donor nephrectomy: standard laparoscopic donor nephrectomy (LDN) and hand-assisted laparoscopic donor nephrectomy (HALDN). In this study we report the operative statistics and donor complications associated with LDN and HALDN from large-center peer-reviewed publications. Methods. We conducted PubMed and Ovid searches to identify LDN and HALDN outcome studies that were published after 2004. Results. There were 37 peer-reviewed studies, each with more than 150 patients. Cumulatively, over 9000 patients were included in this study. LDN donors experienced a higher rate of intraoperative complications than HALDN donors (5.2% versus. 2.0%, 𝑃<.001). Investigators did not report a significant difference in the rate of major postoperative complications between the two groups (LDN 0.5% versus HALDN 0.7%, 𝑃=.111). However, conversion to open procedures from vascular injury was reported more frequently in LDN procedures (0.8% versus 0.4%, 𝑃=.047). Conclusion. At present there is no evidence to support the use of one laparoscopic approach in preference to the other. There are trends in the data suggesting that intraoperative injuries are more common in LDN while minor postoperative complications are more common in HALDN.